Integração da população às margens das rodovias no contexto do processo construtivo e sua respectiva interação urbana e social - Maia, Antonio Sergio de Carvalho (2004)
This paper proposes, fundamentally, to investigate the process of social degradation in populations along roacis and highways, identifying reasons and seeking for solutions to reduce the negative impacts, stimulating the discussion on redeeming affected cornmunities and promoting their inclusion in social and economic Brazilian scene. Through individual interviews, an empirical research was elaborated with the purpose of indicate how to achieve desired life quality and how to integrate the marginal inhabitants in the environment as an undeniable evidence of conciliation and harmony, searching for sustainable development. To make this transformation available, Government and respective Legislation ought to be partners in this issue, in order to create and diffuse opportunities for the community.